2018
DOI: 10.1302/0301-620x.100b5.bjj-2017-1279
|View full text |Cite
|
Sign up to set email alerts
|

The inter- and intraobserver reliability for the radiological parameters of flatfoot, before and after surgery

Abstract: The following parameters can be recommended. For preoperative and postoperative evaluation of flatfoot: anteroposterior, talonavicular coverage angle; lateral, talometatarsal I angle, calcaneal pitch angle, and cuneiform-medial height (high interobserver reliability); and anteroposterior, talometatarsal II angle; lateral, talocalcaneal angle,tibiocalcaneal angle (moderate interobserver reliability). For more experienced observers, we also recommend the anteroposterior talometatarsal I angle (moderate reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
1
19
1
1
Order By: Relevance
“…As shown in Table 5, the implant in situ group presents better surgical outcomes than the extrusion group. Bock et al reported a high inter-observer reliability in the anteroposterior talonavicular angle, lateral talometatarsal 1 angle, and calcaneal pitch angle preoperatively and postoperatively [14]. We are thus convinced that our study further confirms the improvement of foot alignment based on Bock et al’s recommended radiographic parameter.…”
Section: Discussionsupporting
confidence: 76%
“…As shown in Table 5, the implant in situ group presents better surgical outcomes than the extrusion group. Bock et al reported a high inter-observer reliability in the anteroposterior talonavicular angle, lateral talometatarsal 1 angle, and calcaneal pitch angle preoperatively and postoperatively [14]. We are thus convinced that our study further confirms the improvement of foot alignment based on Bock et al’s recommended radiographic parameter.…”
Section: Discussionsupporting
confidence: 76%
“…We observed comparable measurements for standardized radiographic parameters of flatfoot, as well as excellent and good to excellent reliability for measurements using DRR, consistent with values reported in previous studies using XR. 3,18,[20][21][22]27,28 In a cohort of 72 patients who underwent operative correction for PCFD, measurements made using DRR generated from preoperative WBCT were comparable to measurements from preoperative XRs taken during each patient's evaluation. All parameters measured were within the previously published ranges typical for PCFD.…”
Section: Discussionmentioning
confidence: 87%
“…In our study, we utilized calcaneal pitch angle, talonavicular coverage angle, and lateral talus–first metatarsal angle (Meary angle) as the radiographic parameters to evaluate adult acquired flatfoot deformity (AAFD) because these measurements have been shown to have high inter- and intraobserver reliability both before and after reconstructive surgery. 2 We used the C1 Cobb angle to analyze change of orientation of the first tarsometatarsal joint of Cotton osteotomy. Although data are lacking regarding the reliability of the C1 Cobb angle, the angle does describe the articulations of medial cuneiform and directly affects the alignment of the first metatarsal.…”
Section: Materials and Methods Sectionmentioning
confidence: 99%